Pengaruh Return On Asset (ROA) Terhadap Harga Saham PT.Bank Central Asia,Tbk - Batara, Mince; Heriani, Heriani; Pali, Elisabet (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
This study aims to determine the effect of Return On Assets (ROA) on the stock price of PT. Bank Central Asia ,Tbk for the 2016-2020 period. This type of research is quantitative descriptive research, quantitative descriptive research is the calculation of data in the form of the 2016-2020 annual financial statements of PT. Bank Central Asia,Tbk which is published through the IDX official website. Descriptive research method is collecting and analyzing data. The type of data used is secondary data in the form of data in the form of documents obtained from the official website of the Indonesia Stock Exchange (IDX). The data analysis technique was carried out by simple linear regression analysis, Y = a + bX. The results of simple linear regression analysis show Y = 53178,676 – 9198,529X. Testing the hypothesis with a partial test, ROA has a negative and insignificant effect on stock prices. The coefficient of determination R-square (R2) is 0.094. This means that the ability of the independent variable, namely ROA, in explaining the dependent variable, namely the stock price, is 9.4% while the other 90.6% is influenced or explained by other factors that are not included in the variables studied in this study.